2020
DOI: 10.1155/2020/6594306
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Friction Force for Slurry Pipe Jacking considering Soil‐Slurry‐Pipe Interaction

Abstract: This paper aims to provide a new approach to predict the friction resistance of slurry pipe jacking. Friction force usually constitutes the main component of jacking force. It can be calculated by multiplying an effective friction coefficient and the normal force acting on the external surface of the pipe. This effective friction coefficient is introduced to reflect the effect of contact state of pipe soil slurry, highly affected by the effect of lubrication and the interaction of pipe soil slurry. Firstly, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Lubrication: Lubrication is a key factor in reducing frictional resistance; therefore, lubrication has a significant impact on frictional resistance [1,23,24]. 2.…”
Section: Resistance Analysis During Pipe Jacking Construction Based O...mentioning
confidence: 99%
See 2 more Smart Citations
“…Lubrication: Lubrication is a key factor in reducing frictional resistance; therefore, lubrication has a significant impact on frictional resistance [1,23,24]. 2.…”
Section: Resistance Analysis During Pipe Jacking Construction Based O...mentioning
confidence: 99%
“…Pipe-soil contact: Pipe-soil contact increases frictional resistance, but the specific proportion depends on the degree and conditions of the pipe-soil contact [7,16,24,25].…”
Section: Resistance Analysis During Pipe Jacking Construction Based O...mentioning
confidence: 99%
See 1 more Smart Citation
“…And many monitoring results showed that the jacking force is much smaller than the jacking force calculated by this model. If that the pipe was completely covered by slurry sleeve in the process of pipe jacking, Ye et al [15] proposed a solid-liquid contact model to calculate the pipe jacking force. Zhang et al [16] divided the contact outside the pipe into the pipe-soil contact and the pipe-slurry-soil contact to calculate the contact friction force of the two parts, respectively.…”
Section: Calculation and Monitoring Of The Pipe Jacking Forcementioning
confidence: 99%
“…The initial segment solely analyzed pipe–soil contact, asserting that frictional resistance equated to the earth pressure on the pipe jacking multiplied by the pipe–soil friction coefficient 1 – 5 . In the subsequent phase, exclusive attention was directed towards pipe–slurry contact, involving an assessment of thixotropic slurry as a power-law fluid and utilizing a fluid flat model to compute the pipe–slurry shear stress 6 , 7 . The final part encompassed both pipe–soil and pipe–slurry contact analyses, presuming that thixotropic slurry could not entirely envelop the pipe sections, thus maintaining contact with both soil and slurry during pipe jacking 8 12 .…”
Section: Introductionmentioning
confidence: 99%